C-H Bond Activation by an Antimony(V) Oxo Intermediate Accessed through Electrochemical Oxidation of Antimony(III) Tetrakis(thiocyano)corrole - Pain T.; Singh A.K.; Tarai A.; Mondal S.; Indra A.; Kar S. (My University, 2025)
A new class of antimony(III) corroles has been described. The photophysical properties of these newly synthesized tetrakis(thiocyano)corrolatoantimony(III) derivatives having four SCN groups on the bipyrrole unit of corrole are drastically altered compared to their β-unsubstituted corrolatoantimony(III) analogues. The UV-vis and emission spectra of tetrakis(thiocyano)corrolatoantimony(III) derivatives are significantly red-shifted (roughly 30-40 nm) in comparison with their β-unsubstituted corrolatoantimony(III) derivatives. The Q bands are significantly strengthened. The intensity of the most prominent Q band is roughly 70% that of the Soret band and absorbs strongly at the far-red region, i.e., at 700-720 nm. These molecules emit light in the near-infrared region (700-900 nm). Tetrakis(thiocyano)corrolatoantimony(III) undergoes electrochemical anodic oxidation to form SbV═O species, which facilitates electrocatalytic oxygen evolution reaction (OER) and the activation of benzylic C-H to produce benzoic acid selectively. Under optimized conditions, SbIII-corrole@NF (NF = nickel foam) required an overpotential of 380 mV to reach a 50 mA cm-2 current density, comparable with those of other transition-metal-based complexes. On the other hand, replacing the anodic OER with benzyl alcohol oxidation lowered the required potential by 150 mV (at 300 mA cm-2) to improve the energy efficiency of the electrochemical process. © 2023 American Chemical Society.